Proceedings of the Twenty-Seventh Annual ACM-SIAM Symposium on Discrete Algorithms 2015
DOI: 10.1137/1.9781611974331.ch124
|View full text |Cite
|
Sign up to set email alerts
|

Independence and Efficient Domination on P6-free Graphs

Abstract: In the Maximum Weight Independent Set problem, the input is a graph G, every vertex has a nonnegative integer weight, and the task is to find a set S of pairwise non-adjacent vertices, maximizing the total weight of the vertices in S. We give an n O(log 2 n)time algorithm for this problem on graphs excluding the path P 6 on 6 vertices as an induced subgraph. Currently, there is no constant k known for which Maximum Weight Independent Set on P k -free graphs becomes NP-complete, and our result implies that if s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Recently, Lokshtanov et al [26] proved that MWIS can be solved for P 5 -free graphs in polynomial time, and Lokshtanov et al [25] proved that MWIS can be solved for P 6 -free graphs in quasi-polynomial time n O(log 2 n) . A natural open problem is whether MWIS can be solved for P k -free graphs in polynomial time for k ≥ 6 or in quasipolynomial time for k ≥ 7 − even though some characterizations of P k -free graphs and some progress are known in the literature [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Lokshtanov et al [26] proved that MWIS can be solved for P 5 -free graphs in polynomial time, and Lokshtanov et al [25] proved that MWIS can be solved for P 6 -free graphs in quasi-polynomial time n O(log 2 n) . A natural open problem is whether MWIS can be solved for P k -free graphs in polynomial time for k ≥ 6 or in quasipolynomial time for k ≥ 7 − even though some characterizations of P k -free graphs and some progress are known in the literature [13].…”
Section: Discussionmentioning
confidence: 99%
“…However Lokshtanov et al [25] recently proved that MWIS can be solved for P 6 -free graphs in quasi-polynomial time n O(log 2 n) . Then − also referring to the conclusions of [26] − a natural open problem is to establish if MWIS can be solved for P k -free graphs in polynomial time for k ≥ 6 or in quasipolynomial time for k ≥ 7, even though some characterizations of P k -free graphs and some progress are known in the literature; see e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The work for P 5 -free graphs [32] follows the same approach, but generalises it, by showing that in P 5 -free graphs one needs to examine only a particular (polynomially-sized) set of potential maximal cliques in the aforementioned algorithm. Subsequent work [31] uses minimal separators and potential maximal cliques in a different way to develop a quasipolynomial-time algorithm for the Independent Set problem in P 6 -free graphs.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Lokshtanov, Pilipczuk and van Leeuwen [24] and independently, Mosca [31] showed that ED is solvable in polynomial time for P 6 -free graphs.…”
Section: Introductionmentioning
confidence: 99%